Fenestration of the common iliac vein: an unusual cause of deep venous thrombus. Issue 4 (9th April 2021) - Dinh, Krystal; Manuel, Lucy; McGill, Alison; Daly, Thomas
Abstract: Iliac venous anomalies are reported in 20.9% of patients; however, fenestration or bifurcation of the common iliac vein only accounts for 0.4% of patients [ 1 ]. Herein, we present and discuss the rare case of an iliofemoral deep vein thrombosis precipitated by a fenestrated left common iliac vein.